Elderly donors double kidney transplantation (DKT) - Méndez-Chacón, Pedro (2005)
Objective: To use both kidneys of an elderly donor in the same receptor and remark the importance of kidney histology as selector method. Materials and Methods: We evaluate the selection and surveillance of 11 patients who received double kidney of cadaver elderly donors. The ten donors’ mean serum creatinine was 1,3 mg/dL, and the mean age was 63 years old (range 56 to 73 years), the receptor’s mean age 53 years. Both kidneys were examined by frozen wedge biopsy. Quantification of damaged tissue was based on defined methodology. Kidneys with moderate microscopic lesions (score 4 to 6/12) were selected for double kidney transplantation. These were implanted extraperitoneally into each iliac fossa with both separate iliac external vessels and bladder-ureters anastomosis. Steroids and mycophenolat-mophetil represented the first line immunosupresor scheme. Results: None of the receptors required post-transplantation hemodialysis. Nine of eleven receptors kept acceptable renal function in two average surveillance years. One receptor with working allograph died with hemorrhagic vascular cerebral disorder 36 months post transplantation and another developed neoplasia 38 months post transplantation. Conclusions: Elderly donor double renal transplantation is a novel option for elderly receptors in our country. We remark renal histology as a donor selection method. Further investigation will show if double renal transplantation increasing nephron mass will be useful to retard or prevent long time chronic allograph dysfunction.